2017
DOI: 10.3390/en10081190
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Effect of Scour on the Loading and Deformation Responses of Monopile Foundations

Abstract: Severe foundation scour may occur around monopile foundations of offshore wind turbines due to currents and waves. The so-called p-y curves method is suggested in the existing design recommendations to determine the behavior of monopiles unprotected against scour and the reduction of effective soil stress is accounted for by the extreme scour depth. This conservative design approach does not consider the geometry of the scour hole and the effect of pile diameter on the soil resistance. An underestimated founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Tuy nhiên việc hiểu biết về kết cấu này còn hạn chế, đặc biệt là trong điều kiện biển Việt nam chưa có một dự án thực tế nào sử dụng. Đặc điểm của Monopile là kết cấu một trụ đơn có độ dự trữ thấp nên khi áp dụng phải xem xét kỹ những tác động của môi trường như ăn mòn, hà bám, xói chân cọc ảnh hưởng đến sự làm việc của kết cấu [11][12][13]. Điều quan tâm là các tác động này có thể dẫn đến việc kết cấu không còn đáp ứng 02 yêu cầu nêu ở trên, đặc biệt về vấn đề dao động.…”
Section: Giới Thiệuunclassified
“…Tuy nhiên việc hiểu biết về kết cấu này còn hạn chế, đặc biệt là trong điều kiện biển Việt nam chưa có một dự án thực tế nào sử dụng. Đặc điểm của Monopile là kết cấu một trụ đơn có độ dự trữ thấp nên khi áp dụng phải xem xét kỹ những tác động của môi trường như ăn mòn, hà bám, xói chân cọc ảnh hưởng đến sự làm việc của kết cấu [11][12][13]. Điều quan tâm là các tác động này có thể dẫn đến việc kết cấu không còn đáp ứng 02 yêu cầu nêu ở trên, đặc biệt về vấn đề dao động.…”
Section: Giới Thiệuunclassified
“…Results indicated that the local scour hole would result in much higher lateral soil resistance for a given depth than for the general scour case, that is, complete removal of the soil surface layer. Tseng et al [77] combined the approach of Sørensen [78] for modifying the initial modulus of subgrade reaction (k py )andtheapproachofLin et al [75] for modifying p ult to evaluate the scour effect on the deformation response of monopile foundations. According to the case analysis, when the p-y curve method suggested by the design guidelines for an offshore wind turbine was used to design the monopile foundation for an OWT, the foundation deformation was underestimated for a scour depth of less than pile diameter, and foundation stiffness was underestimated for a scour depth of greater than pile diameter.…”
Section: Effects Of Local Scour On the Lateral Response Of A Monopilementioning
confidence: 99%
“…Tseng et al [34] discussed the effects of the pile diameter and the scour on the p-y curves and compared various corrections to the formula proposed by other researchers. Among them, Kallehave et al [14] measured the natural frequencies of the support structures of three offshore wind turbines to be higher than those obtained using the p-y curve method recommended in API [8].…”
Section: Load-deformation Response Of the Pile-soil Interactionmentioning
confidence: 99%